ELEMENTS REGULATION DURING CARTILAGE AND BONE DEFORMITY - POTENTIAL CLINICAL INDEX IN EARLY DIAGNOSIS, MONITORING AND PROGNOSIS IN CHILDREN OF KASHIN-BECK DISEASE - Juan, Ma Wei; Xiong, Guo; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2015)
Background: Kashin-Beck Disease (KBD) is a chronic deforming osteoarthritis starting in early childhood and affecting the cartilage metabolism and endochondral ossification. Selenium (Se) deficiency has been postulated as the major environmental etiological factor for KBD by many studies. Other minerals such as the Manganese (Mn) and calcium (Ca) which don’t have uniform distribution in environment are also important elements involved in bone and cartilage formation but their regulation in KBD has been rarely reported. The study was done to investigate the role ofMn and Ca in addition to Se in KBD. Methods: In this study, the Se, Mn and Calevels were investigated in children from different groups (KBD group, Healthy group from KBD endemic areas (inner control group), Healthy group (outer control group) from Non KBD areas and KBD group with selenium supplementation). The contents of Mn, S and Ca in serum and hair were analyzed by inductively coupled plasma mass spectrometry. Results: The increased Mnlevels of serum and hair in KBD children were observed compared with normal groups. The Mn and Ca have similar trends in different groups but Se and Mn displayed reversed trends. Conclusions: The Mn and Ca contributed to KBD pathogenesis combined with se in regulation of growth and development. The relative ratio of Mn to Se can be a potential clinical index in early diagnosis, monitoring and prognosis of KBD in children.